Factors associated with medical device-related pressure injury in an intensive care unit in the Amazon region during the COVID-19 pandemic: retrospective cohort - Sousa, Vitória Alice Alencar; Ferreira, Daniele Nunes da Silva; Mendonça, Giovana Vitória Guimarães; Marinho, Rebecca Lobato; Andrade, Natasha Cristina Oliveira; Soares, Tamires de Nazaré; Silva, Marcos Jessé Abrahão; Lobato, Diana da Costa; dos Santos, Suziane do Socorro; Rodrigues, Yan Corrêa; Sardinha, Daniele Melo; Lima, Luana Nepomuceno Gondim Costa (Frontiers in Medicine, 2025)
Medical device–related pressure injuries (MDRPIs) pose a serious public health challenge, particularly in intensive care settings during the COVID-19 pandemic. This retrospective cohort study aimed to characterize the profile and identify risk and protective factors for MDRPIs among adult ICU patients in a metropolitan region of the Amazon between January 2021 and December 2022. We reviewed 603 medical records—31 patients (5.1%) developed MDRPIs and 572 did not—and applied chi-square tests, normality assessments, Mann–Whitney U-tests, binary logistic regression, and Kaplan–Meier survival analysis. Ethical approval was obtained from the Fundação Hospital de Clínicas Gaspar Viana Ethics Committee (approval no. 5,991,542). Independent risk factors for MDRPIs included chronic obstructive pulmonary disease (OR 19.33; 95% CI 2.92–127.73; p = 0.002), orotracheal tube use (OR 19.00; p = 0.002), nasal catheter use (OR 3.33; 95% CI 1.32–8.40; p = 0.011), and longer hospital stay (OR 1.09 per day; 95% CI 1.05–1.12; p < 0.001). Protective factors were systemic arterial hypertension (OR 0.22; 95% CI 0.08–0.58; p = 0.009), higher Braden scale scores (OR 0.22 per point; 95% CI 0.08–0.58; p = 0.002), and invasive arterial blood pressure monitoring (OR 0.14; 95% CI 0.03–0.79; p = 0.025). Survival analysis demonstrated that patients with MDRPIs had significantly longer hospital stays and higher mortality rates (Breslow p = 0.007; log-rank p = 0.041; Tarone–Ware p = 0.011). This first study of MDRPIs in the Amazon region highlights key modifiable factors and underscores the need for enhanced nursing protocols and working conditions to prevent device-related pressure injuries in critical care. These findings can guide continuing education initiatives and policy development in critical care nursing.